Fluktuasi Asimetri dan Abnormalitas Ikan Jelawat (Leptobarbus hoevenii Blkr.) Hasil Pemijahan Semi Intensif - Ghofur, Muarofah; Syahrizal, Syahrizal; Sugihartono, Muhammad; Burrahman, Inal (Universitas Batangahari Jambi, 2024)
Jelawat fish (Leptobarbus hoevenii Blkr.) is one of the fish that is in great demand by the public. This production has problems with the body shape of fish fry which has many asymmetries and abnormalities. The cause of this cannot be ascertained, but the assumption is due to the influence of high pressure and water currents. For this reason, there needs to be clear research so that the exact cause is known. This study aims to see the fluctuations of asymmetry and abnormality in jelawat fish (L. hoeveni Blkr.) as a result of semi-intensive spawning. This research method is a sampling method on fish from semi-intensive spawning that is 2-3 cm in size. Then meristic measurements were taken and asymmetric fluctuations and abnormalities were calculated. The results of the study found that the value of number asymmetric fluctuations (FAn) ranged from 0.451 to 0. 864, while the magnitude asymmetric fluctuation (FAm) ranges from -0.044-0.053. For an abnormality of 1.05%, absolute length growth of 3.15 cm/head, absolute weight growth of 0.55 grams/head and survival rate of jellyfish larvae 99.5%.%, The results of water quality measurements were temperature range from 26-28.1oC, pH 6.7-7, dissolved oxygen of 4.7-5.3 mg/L, carbon dioxide of 5.3-8 mg/L and ammonia content in maintenance water of 0.001-0.011.